Epigenetic Therapy of Cancer 2013
DOI: 10.1007/978-3-642-38404-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase (HDAC) Inhibitors in Recent Clinical Trials for Cancer Therapy

Abstract: Heritable changes in gene expression that are not based upon alterations in the DNA sequence are defined as epigenetics. The most common mechanisms of epigenetic regulation are the methylation of CpG islands within the DNA and the modification of amino acids in the N-terminal histone tails. In the last years, it became evident that the onset of cancer and its progression may not occur only due to genetic mutations but also because of changes in the patterns of epigenetic modifications. In contrast to genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Histone deacetylase inhibitors (HDACis) exert their anticancer effects by increasing acetylation of core histones as well as non-histone proteins, thereby influencing gene transcription and ultimately leading to the induction of apoptosis, differentiation or degradation of misfolded proteins [ 7 ]. To date, three HDACis, vorinostat (SAHA), romidepsin and panobinostat (LBH-589, PS), have been FDA-approved for the treatment of cutaneous and peripheral T-cell lymphoma and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Histone deacetylase inhibitors (HDACis) exert their anticancer effects by increasing acetylation of core histones as well as non-histone proteins, thereby influencing gene transcription and ultimately leading to the induction of apoptosis, differentiation or degradation of misfolded proteins [ 7 ]. To date, three HDACis, vorinostat (SAHA), romidepsin and panobinostat (LBH-589, PS), have been FDA-approved for the treatment of cutaneous and peripheral T-cell lymphoma and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, epigenetic inhibitors have often shown weak efficacy when used as single agents. 44 Hence, combination therapy might prove to be the key to successful implementation of epigenetic inhibitors in cancer treatment. The anthracycline doxorubicin is a well-characterized DNA-intercalating drug that is used in the therapy of neuroblastoma, combined with cisplatin, etoposide and cyclophosphamide (CEDC regime).…”
Section: Resultsmentioning
confidence: 99%
“…This points out to a potential use of HAT inhibitors in combination chemotherapy. For HDAC inhibitors, many such combinations are currently studied in clinical trials 44 and a systematic analysis of synergies of HAT inhibitors with other epigenetic agents but also other classic anticancer drugs is warranted. Furthermore, PU139-treated healthy mice showed significant histone hypoacetylation in bone marrow on all four investigated lysine residues in a short-time exposure experiments confirming target engagnement in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylases (HDACs) are some of the best-studied histone modifying enzymes within the still expanding field of epigenetics. They are validated targets for anticancer therapy with five approved drugs on the market and a growing number of HDAC inhibitors in promising clinical trials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Besides the Sirtuins (class III HDACs) that possess a catalytic mechanism depending on NAD (nicotine adenine dinucleotide), the classical HDACs (classes I, II and IV) are zinc-dependent amidohydrolases.…”
Section: Introductionmentioning
confidence: 99%